2009
DOI: 10.1667/rr1143.1
|View full text |Cite
|
Sign up to set email alerts
|

The Elimination of Low-Dose Hyper-radiosensitivity by Transfer of Irradiated-Cell Conditioned Medium Depends on Dose Rate

Abstract: Irradiation of T-47D cells with 0.3 Gy delivered by a (60)Co source at a low dose rate of 0.3 Gy/h abolished low-dose hyper-radiosensitivity (HRS) for at least 14 months (with continuous cell culturing), while the same dose administered acutely (40 Gy/h) eliminated HRS for less than 24 h. Medium transferred from the low-dose-rate primed cells (low-dose-rate ICCM) to unirradiated cells eliminated HRS in recipient cells even if the donor cells had been cultivated for 14 months after the priming dose. Thus low-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 46 publications
5
36
0
Order By: Relevance
“…Hence, HRS-negative H460 cells showed increased clonogenic inhibition than apoptosis when compared with HRS-positive H-157 cells. However, UKY-29 and A549 cells harboring HRS did not show significant induction of apoptosis following LDFRT, thus supporting the previous observations that apoptosis may be indicative of HRS but is not a prerequisite for HRS (37,38). Furthermore, in H460 cells, significant differences in the expression of genes related to apoptosis were not observed with any of the treatments when compared with the untreated group (Supplementary Table 6).…”
Section: Discussionsupporting
confidence: 85%
“…Hence, HRS-negative H460 cells showed increased clonogenic inhibition than apoptosis when compared with HRS-positive H-157 cells. However, UKY-29 and A549 cells harboring HRS did not show significant induction of apoptosis following LDFRT, thus supporting the previous observations that apoptosis may be indicative of HRS but is not a prerequisite for HRS (37,38). Furthermore, in H460 cells, significant differences in the expression of genes related to apoptosis were not observed with any of the treatments when compared with the untreated group (Supplementary Table 6).…”
Section: Discussionsupporting
confidence: 85%
“…In previous studies (Edin et al 2007, Edin et al 2009, T-47D breast cancer cells were found to display a pronounced low-dose hyper-radiosensitivity when irradiated acutely (40 Gy/h) with 60 Co g-rays. Surprisingly, irradiating the cells with a priming dose of 0.3 Gy at the low dose-rate (LDR) of 0.3 Gy/h was found to eliminate HRS permanently, i.e., the cells did not show a HRS response to subsequent acute irradiation given up to 14 months (with continuous culturing of the cells) after the LDR priming dose (Edin et al 2009).…”
Section: Introductionmentioning
confidence: 92%
“…Surprisingly, irradiating the cells with a priming dose of 0.3 Gy at the low dose-rate (LDR) of 0.3 Gy/h was found to eliminate HRS permanently, i.e., the cells did not show a HRS response to subsequent acute irradiation given up to 14 months (with continuous culturing of the cells) after the LDR priming dose (Edin et al 2009). If the priming dose of 0.3 Gy was given as an acute irradiation (i.e., at a dose-rate of 40 Gy/h), HRS was eliminated only transiently (less than 24 h) (Edin et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations